2018
DOI: 10.1111/bjh.15399
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic haematopoietic cell transplantation for adult acute myeloid leukaemia in second remission: a retrospective study of the Adult Acute Myeloid Leukaemia Working Group of the Japan Society for Haematopoietic Cell Transplantation (JSHCT)

Abstract: To evaluate the outcomes and prognostic factors following allogeneic haematopoietic cell transplantation (HCT) for adult acute myeloid leukaemia (AML) in second complete remission (CR2), we retrospectively analysed the Japanese registration data of 1080 adult AML patients in CR2 who had received allogeneic HCT. The probability of overall survival and the cumulative incidence of relapse at 3 years was 66% and 19%, respectively. In multivariate analysis, older age, poor cytogenetics and shorter duration of first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…We examined the outcomes and prognostic factors for patients who received allogeneic HCT during CR2 and found that the 3-year OS, relapse, and NRM rates were 66%, 19%, and 19%, respectively. Multivariate analysis revealed that advanced age, poor cytogenetics, and shorter CR1 duration, especially when it was <1 year, were predictive of worse OS 23 . The prognosis for patients with multiple relapses is poor.…”
Section: Disease Status At Transplantationmentioning
confidence: 98%
“…We examined the outcomes and prognostic factors for patients who received allogeneic HCT during CR2 and found that the 3-year OS, relapse, and NRM rates were 66%, 19%, and 19%, respectively. Multivariate analysis revealed that advanced age, poor cytogenetics, and shorter CR1 duration, especially when it was <1 year, were predictive of worse OS 23 . The prognosis for patients with multiple relapses is poor.…”
Section: Disease Status At Transplantationmentioning
confidence: 98%